Simetrias de paridade e de reversão temporal no Efeito Hanbury Broen-Twiss - Silva, Erick Rodrigues (2015)
The Hanbury Brown-Twiss experiment is very well established in quantum optics literature, so we devoted this dissertation in order to embed the parity and temporal reversal symmetry in the former experiment. Therefore, we developed the scattering matrix formalism which allow us use some techniques such as the scattering matrices' concatenation of di erent sections in terms of one matrix and the scattering problem of a parity and temporal reverse symmetric system. In this manner, we could derive the scattering matrix of a parity and temporal reverse symmetric Hanbury Brown- Twiss experiment(HBT-PT). With the possession of this matrix, we proposed a theoretical model which provides how to measure the symmetry of this system, which we called correlation functions formalism. In order to stablish the former formalism, we studied B uttiker formalism, which we veri ed how the correlation between 2 incident particles in a system relates to the noise due transport of this particles and what kind of noise we are treating in a given regime which the system is operating. Then, we found the input states in terms of the output states of two particles inciding in a multiterminal system, which we used it's scattering matrix to stablish the relation between the states. Thereat, we derived all the possibles correlations(therefore, the noise) of two incident particles in the former system. Thereby, we analysed the extreme cases of a barrier coupled to the HBT-PT experiment for the purpose of stablish which regime the experiment is symmetric adjusted, so, demonstrating the Hanbury Brown-Twiss E ect with parity and temporal reverse symmetries.